THE INFLUENCE OF THE PRINCIPAL SUPERVISION AND SCHOOL WORK CLIMATE ON THE WORK ETHOS OF STATE ELEMENTARY SCHOOL TEACHERS IN CLUSTER 3 AND 4, LARARAN DISTRICT, TANGERANG CITY - SUMEIDI, Didi (Journal of Education and Leadership in Education, 2023)
The purpose of this study is to investigate: (1) The effect of principal supervision on the work ethic of teachers. (2) The school's work climate is towards the work ethic of teachers. (3) The principal supervised the school's work climate. The research approach used in this study is a quantitative approach. The population in this study was all elementary school teachers in Cluster 3 and 4 of the UPT Primary Education Larangan City area with a sample of 106 teachers who were randomly sampled. The analysis technique used is path analysis technique. Based on the results of the analysis, it is known that: 1) There is a direct positive and significant influence of Principal Supervision on the work ethic. This is evident from the results of the table t-value > t (3,806 > 1.983) and the path efficiency value of 0.335. 2) There is a direct positive and significant influence on the work climate of elementary school teachers. This is evident from the results of the t-value of the table > tcount (3,746> 1.983) and the path coefficient value of 0.329. 3) There is a direct positive and significant influence of Principal Supervision on the work climate. This is evident from the results of the t-value of the table > t(3,677> 1.983) and the coefficient value of the path of 0.339.